The influence of ROA and Sales Growth on Firm Size - Hamzah, Zeze Zakaria; Gursida, Hari; Indrayono, Yohanes (Eastasouth Institute, 2024)
The Industrial Revolution is a time when human work in various fields began to be replaced by machines. This study wants to examine how the effect of Return of Assets and Sales growth on firm size. The population in this study were 263 companies. And observations were made in accordance with the criteria and found a total sample of 40 companies. The data analysis method used in this research is Regression. The results are 1) Return on Assets has a negative effect on financial distress 2) Sales Growth has a negative effect on financial distress is rejected.